Rain-shelter Cultivation Affects the Accumulation of Volatiles in ‘Shuijing’ Grape Berries during Development - Qingyang Sun; Yue Zhao; Shusheng Zhu; Fei Du; Ruzhi Mao; Lijing Liu; Yifan Zhu; Su Li; Meng Sun; Bin Tian (HortScience, 2022)
Rain-shelter cultivation could protect grape berries from many diseases and affect grape berry quality. However, there have been few studies of the effects of rain-shelter cultivation on the accumulation of volatiles in Shuijing grapes grown in Yunnan Province. Therefore, the goal of this research was to explore the effects of rain-shelter cultivation on the accumulation of volatiles in Shuijing grape berries during development. The Shuijing grapes used during this study were grown in the Yunnan Province of southwest China in two consecutive vintages (2018 and 2019). The results showed that rain-shelter cultivation promoted grape ripening and inhibited volatiles synthesis in Shuijing grape berries. However, the application of rain shelters did not affect the accumulation patterns of volatiles; instead, it affected the concentrations of volatiles in Shuijing grape berries, especially during the maturation phase [12–15 weeks after flowering (WAF)]. The concentrations of isoprenoid-derived volatiles (2019), fatty acid-derived volatiles, and amino acid-derived benzenoids in Shuijing grape berries were decreased by rain-shelter cultivation during the maturation phase. The concentration of 2,5-dimethyl-4-methoxy-3(2H)-furanone (mesifurane) was also decreased by rain-shelter cultivation during the late maturation phase (14 and 15 WAF). A principal component analysis (PCA) indicated that the vintage had a much greater influence on the physicochemical parameters and volatiles of the Shuijing grape berries than the cultivation method. This work reveals the formation and accumulation patterns of volatiles of Shuijing grape berries under rain-shelter cultivation during development and has significance for exploring the potential of rain-shelter cultivation in grape-producing regions with excessive rainfall.